Analysis of S-commerce purchasing experiences of Filipino fabric consumers during the Covid-19 pandemic - Malubag, Allysa Margarette (College of Home Economics, University of the Philippines Diliman, 2023)
The Covid-19 pandemic, which started in 2020, limited the mobility of people outside of their homes and quarantine areas which caused consumers to shift towards shopping online making online selling platforms popular. Just like many other industries, the apparel and textile industry was greatly affected. Some fabric shops switched to Social Commerce (S-commerce) in order to expand their sales channels through social networking sites. However, as these sellers started to shift to a ‘new normal’ business operation, the shift in online consumer needs should also be taken into consideration. This study aims to analyze the consumer experiences of online fabric shoppers in Metro Manila during the pandemic period. Specifically, it aims to describe the experiences of fabric buyers when purchasing fabrics online, identify factors that contributed positively and negatively to their experience, and determine the visual and textual information that these consumers need for online fabricpurchase in order to provide recommendations on how these experiences can be improved. The study is descriptive in nature and will gather quantitative data through structured online survey from respondents selected using stratified purposive sampling from the three purposely selected Facebook groups namely Fabric and Sewing Needs Philippines, Tela Tela Bodega Price, and Online Tela Pabili. Respondents should be residing in Metro Manila and should have at least one finished buying transaction in an online fabric shop. Questions in the online survey are structured based on the five stages of consumer buying behavior. The gathered data will be analyzed through measures of frequency and thematic analysis to describe the respondents’ online purchasing experience and to identify visual and textual information they find necessary in the online purchase of fabric.